Cis- and Trans-variations of Stearoyl-CoA Desaturase Provide New Insights into the Mechanisms of Diverged Pattern of Phenotypic Plasticity for Temperature Adaptation in Two Congeneric Oyster Species. (20th January 2023) - Wang, Chaogang; Li, Ao; Cong, Rihao; Qi, Haigang; Wang, Wei; Zhang, Guofan; Li, Li
Abstract: The evolution of phenotypic plasticity plays an essential role in adaptive responses to climate change; however, its regulatory mechanisms in marine organisms which exhibit high phenotypic plasticity still remain poorly understood. The temperature-responsive trait oleic acid content and its major gene stearoyl-CoA desaturase ( Scd ) expression have diverged in two allopatric congeneric oyster species, cold-adapted Crassostrea gigas and warm-adapted Crassostrea angulata . In this study, genetic and molecular methods were used to characterize fatty acid desaturation and membrane fluidity regulated by oyster Scd . Sixteen causative single-nucleotide polymorphisms (SNPs) were identified in the promoter/ cis -region of the Scd between wild C. gigas and C. angulata . Further functional experiments showed that an SNP (g.-333C [ C. gigas allele] >T [ C. angulata allele]) may influence Scd transcription by creating/disrupting the binding motif of the positive trans -factor Y-box factor in C. gigas / C. angulata, which mediates the higher/lower constitutive expression of Scd in C. gigas / C. angulata . Additionally, the positive trans -factor sterol-regulatory element–binding proteins ( Srebp ) were identified to specifically bind to the promoter of Scd in both species, and were downregulated during cold stress in C. gigas compared to upregulated in C. angulata . This partly explains the relatively lower environmental sensitivity (plasticity) of Scd in C. gigas . This study serves as an experimental case to reveal that both cis - and trans -variations shape the diverged pattern of phenotypic plasticity, which provides new insights into the formation of adaptive traits and the prediction of the adaptive potential of marine organisms to future climate change.